Stable C and N isotope abundances in water-extractable organic matter from air-dried soils as potential indices of microbially utilized organic matter - Nagano, Hirohiko; Atarashi-Andoh, Mariko; Tanaka, Sota; Yomogida, Takumi; Kozai, Naofumi; Koarashi, Jun (Frontiers in Forests and Global Change, 2023)
Stable carbon (C) and nitrogen (N) isotopes (13C and 15N) in water-extractable organic matter (WEOM) derived from air-dried soils may be applicable to elucidate microbial decomposition of soil organic matter (SOM) crucial in terrestrial C cycles. Forty soil samples were collected from a depth of 0–6 cm in a Japanese temperate broadleaved forest, with vegetation succession from grassland approximately 150 years ago. Those soil samples were air-dried before the water extraction and organic matter analysis. The C and N concentrations of WEOM were less than 3.6% of those of the bulk soil, and were positively correlated with those of bulk soil at p < 0.01. Positive correlation between the two fractions (i.e., WEOM and bulk soils) was also found for natural 13C and 15N abundances (δ13C and δ15N; p < 0.01). However, the C/N ratio of WEOM was little correlated with that of bulk soils, exhibiting a narrow range of values around 10. Thus, those features of the WEOM were similar to the well-known features of microbial biomass. The δ13C and δ15N enrichments in WEOM relative to bulk soil, the difference in stable isotope abundances between bulk SOM and WEOM, were negatively and positively correlated, respectively, with the concentrations of organo-mineral complexes and short-range order minerals (non-crystalline oxyhydroxides of aluminum and iron, allophane, imogolite, and allophane-like constituents), which play significant roles in SOM stabilization in soils. These relationships suggested that the stable isotopic enrichments in WEOM can be a good indicator of the microbial utilization of soil C and N under different substrate availabilities, which are crucial in SOM decomposability varying from local to global scales.